Impact of Early-Life Microbiota on Immune System Development and Allergic Disorders - Norbert Dera; Katarzyna Kosińska-Kaczyńska; Natalia Żeber-Lubecka; Robert Brawura-Biskupski-Samaha; Diana Massalska; Iwona Szymusik; Kacper Dera; Michał Ciebiera (Biomedicines)
Introduction: The shaping of the human intestinal microbiota starts during the intrauterine period and continues through the subsequent stages of extrauterine life. The microbiota plays a significant role in the predisposition and development of immune diseases, as well as various inflammatory processes. Importantly, the proper colonization of the fetal digestive system is influenced by maternal microbiota, the method of pregnancy completion and the further formation of the microbiota. In the subsequent stages of a child’s life, breastfeeding, diet and the use of antibiotics influence the state of eubiosis, which determines proper growth and development from the neonatal period to adulthood. The literature data suggest that there is evidence to confirm that the intestinal microbiota of the infant plays an important role in regulating the immune response associated with the development of allergic diseases. However, the identification of specific bacterial species in relation to specific types of reactions in allergic diseases is the basic problem. Background: The main aim of the review was to demonstrate the influence of the microbiota of the mother, fetus and newborn on the functioning of the immune system in the context of allergies and asthma. Methods: We reviewed and thoroughly analyzed the content of over 1000 articles and abstracts between the beginning of June and the end of August 2024. Over 150 articles were selected for the detailed study. Results: The selection was based on the PubMed National Library of Medicine search engine, using selected keywords: “the impact of intestinal microbiota on the development of immune diseases and asthma”, “intestinal microbiota and allergic diseases”, “the impact of intrauterine microbiota on the development of asthma”, “intrauterine microbiota and immune diseases”, “intrauterine microbiota and atopic dermatitis”, “intrauterine microbiota and food allergies”, “maternal microbiota”, “fetal microbiota” and “neonatal microbiota”. The above relationships constituted the main criteria for including articles in the analysis. Conclusions: In the present review, we showed a relationship between the proper maternal microbiota and the normal functioning of the fetal and neonatal immune system. The state of eubiosis with an adequate amount and diversity of microbiota is essential in preventing the development of immune and allergic diseases. The way the microbiota is shaped, resulting from the health-promoting behavior of pregnant women, the rational conduct of the medical staff and the proper performance of the diagnostic and therapeutic process, is necessary to maintain the health of the mother and the child. Therefore, an appropriate lifestyle, rational antibiotic therapy as well as the way of completing the pregnancy are indispensable in the prevention of the above conditions. At the same time, considering the intestinal microbiota of the newborn in relation to the genera and phyla of bacteria that have a potentially protective effect, it is worth noting that the use of suitable probiotics and prebiotics seems to contribute to the protective effect.